-48=9p-3

Simple and best practice solution for -48=9p-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -48=9p-3 equation:


Simplifying
-48 = 9p + -3

Reorder the terms:
-48 = -3 + 9p

Solving
-48 = -3 + 9p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-9p' to each side of the equation.
-48 + -9p = -3 + 9p + -9p

Combine like terms: 9p + -9p = 0
-48 + -9p = -3 + 0
-48 + -9p = -3

Add '48' to each side of the equation.
-48 + 48 + -9p = -3 + 48

Combine like terms: -48 + 48 = 0
0 + -9p = -3 + 48
-9p = -3 + 48

Combine like terms: -3 + 48 = 45
-9p = 45

Divide each side by '-9'.
p = -5

Simplifying
p = -5

See similar equations:

| 3(4x-2)-12x+4=7 | | 2x+3-4x=-10 | | 143-4x=23+17 | | 7x+4=14x+16 | | 12=-w | | 6-24=14y-5 | | 35=3(3n+5)-5n | | 4(8+6k)=-64 | | 24x+7-27x=2-7 | | X^2+16x-60=0 | | 44-4x=44-4x | | -2w^2+7w-6=0 | | 24=3(8+8k) | | 343.57x+-1.35=300 | | -x+4=-5-x | | y=3+.25x | | 5(1-6n)=-55 | | 2-f=10 | | 2x+3(x-9)-2(x-3)=0 | | 71=-6(3x+5)-7 | | y+10.5=9.4 | | x^3-x=90 | | 19n+11= | | x-3=-4.5 | | 21.78=4g+3.62 | | 2w-5w=18 | | 5x=120-5x | | 3(b+3)=3(2b-6) | | 12+5k=6(k+2) | | ysquared+4y-12=0 | | 1.33x+1.33(2x-15)=3.5 | | 4[a-(3a-4)]=a+5 |

Equations solver categories